A invenção da brasileira: uma história sobre imagem feminina e turismo - Pinto, Renata Pires (2015)
This research discusses the women body as a symbolic construction, focusing on the interference that the print and audiovisual vehicles had at the manufacture a national identity, reinforcing the stereotype of well shapely bodies, bearing a kind of natural sensuality and sexuality of Brazilian women. The main purpose of this text is to identify and analyze on advertising vehicles, produced for foreign audiences, what are the speeches about woman bodies, which historically asserted the Brazilian woman stereotype. To do so, is used as primary source the advertising materials produced by Embratur (Brazilian Institute of Tourism), the official governmental institute that is responsible on promoting Brazilian tourism to foreign tourists as well as materials produced by companies that are related to Embratur. It s intent to unfold part of the historical construction of this feminine image and how the Brazilian woman image was linked into the tourism industry in advertising materials. Assuming that the cultural analysis of the female body emerges as an important issue in the field of humanities, the focus on body image can be viewed as a key element in discussions about the construction of identities, in a way to problematize the idea of a fixed and essentialized female identity, demonstrating that this stereotype is not enough to define the woman category nowadays